WEB-BASED USED CLOTHES SALES - Pratama, Ferdianto; Apriansyah; Haryanto, Dedi (CV SWA Anugerah, 2024)
The rapid development of information technology affects the way we search for and transact information, especially in online buying and selling. In Indonesia, the second branded industry still relies on direct sales methods, which often result in low prices and accessibility constraints for buyers. The main obstacle is the offline transaction process that requires buyers to be physically present. To overcome this problem, the implementation of a web-based online store information system application is expected to improve sales efficiency and allow buyers to shop remotely. Currently, second-branded businesses in Palembang run two sales methods, namely offline and live streaming. This research aims to improve the quality of second-branded sales services in Palembang through a more efficient web-based information system. With this method, buyers can access and transact easily through an online platform, avoiding the difficulties faced in the less efficient traditional offline and live streaming methods. The implementation of a web-based sales information system will hopefully allow buyers to browse products, obtain information, and conduct transactions more conveniently and efficiently. Thus, second-branded businesses can expand their market and increase their revenue, while providing a better shopping experience for buyers.